Kebijakan Indonesia Dalam Melakukan Penyelamatan Lingkungan Dari Dampak Emisi Pelayaran Internasional Di Alur Laut Kepulauan Indonesia - Deflides, Viani Ghefira; Ardiyanto, Syaifullah Yophi; Hidayat, Tengku Arif (Peneliti.net, 2024)
Article 1 number 3 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System has a weakness in that children under 12 (twelve) years of age are not included in the categorization of children in conflict with the law so they cannot be held criminally responsible and diverted. However, in many cases, children under 12 (twelve) years old can be perpetrators of criminal acts. When viewed from a humanitarian and moral perspective, it is unfair for victims who experience physical, mental suffering and/or economic loss if the perpetrator cannot be held criminally responsible, especially if the victim is also a child. Therefore, legal reform is needed in the categorization of children in conflict with the law. The aim of this research is, first, to determine and analyze the urgency of the idea of ​​categorizing children in conflict with the law, and second, to formulate the idea of ​​categorizing children in conflict with the law in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This research is normative legal research or also called doctrinal legal research. Research was carried out on legal theories, namely justice and legal reform, as well as a systematic approach to law. The data sources used are statutory regulations, books, journals, scientific works, dictionaries and official websites. This research also uses qualitative analysis and produces descriptive data. Based on the research conducted, there are 2 (two) conclusions obtained. First, the urgency of the idea of ​​categorizing children in conflict with the law which includes children under 12 (twelve) years of age who have the potential to commit criminal acts due to several factors; and the absence of criminal accountability and diversion causes victims to receive different treatment. Second, the idea of ​​categorizing a child in conflict with the law is someone who is not yet 18 (eighteen) years old who is suspected of committing a criminal act. The suggestion from the results of this research is, first, Article 1 number 3 of the Juvenile Criminal Justice System Law needs to be revised with this idea in mind. Second, there is a need for regulations that clarify the criminal procedural law for children so as not to cause confusion after the revision of the categorization of children in conflict with the law in the Juvenile Criminal Justice System Law so that the rights of children in conflict with the law remain protected, especially children in conflict with the law and the victim.